Regulatory mechanism of heat-active retrotransposons by the SET domain protein SUVH2 - Niu, Xiaoying; Ge, Zhiyu; Ito, Hidetaka (Frontiers in Plant Science, 2024)
New transposon insertions are deleterious to genome stability. The RNA-directed DNA methylation (RdDM) pathway evolved to regulate transposon activity via DNA methylation. However, current studies have not yet clearly described the transposition regulation. ONSEN is a heat-activated retrotransposon that is activated at 37°C. The plant-specific SUPPRESSOR OF VARIEGATION 3–9 HOMOLOG (SUVH) family proteins function downstream of the RdDM pathway. The SUVH protein families are linked to TE silencing by two pathways, one through DNA methylation and the other through chromatin remodeling. In this study, we analyzed the regulation of ONSEN activity by SUVH2. We observed that ONSEN transcripts were increased; however, there was no transpositional activity in Arabidopsis suvh2 mutant. The suvh2 mutant produced siRNAs from the ONSEN locus under heat stress, suggesting that siRNAs are involved in suppressing transposition. These results provide new insights into the regulatory mechanisms of retrotransposons that involve siRNA in the RdDM pathway.